Conception Rates of Holstein-Friesian Cows Inseminated Artificially with Reducing Frozen Semen Doses - Anneke Anggraeni; T. Herawati; L. Praharani; D. Utami; A. Argis (Faculty of Animal Science, Bogor Agricultural University, 2016)
Conception rates of Holstein Friesian (HF) acceptors were evaluated in artificial insemination (AI) mating using three frozen semen doses of the straws per volume of 0.25 cc. Frozen semen consisted of a standard dose by 25 x 106 sperms (L.1) and two reduced doses by 20 x 106 sperms (L.2) and 15x106 sperms (L.3). This field study was conducted in dairy cattle area of Lembang NBMCU, from August 2011 to March 2012. Frozen semens were obtained from two HF national progeny tested young bulls. Conception was detected by rectal palpation, around 60-90 days after AI mating. Conception rates (CR %) were calculated as a ratio between pregnant acceptors to the total AI mated cows. Some general linear model analyzes were conducted by considering fixed variables of semen dose (3), bull (2), inseminator (6) and parity (5). The results showed that three frozen semen doses did not significantly affect (P>0.05) on CR (%). By decreasing semen dose to L.3 gave CR (%) similar to L2 even to L1. It was concluded that frozen semen doses of HF bulls at the levels of 20 million to 15 million sperms per straw per volume of 0.25 cc resulted CR (%) similar to the standard one.